6 Efficacy of endovascular thrombectomy in patients with M2 segment middle cerebral artery occlusions: meta-analysis of data from the HERMES collaboration. (July 2018) - Menon, B; Brown, S; Almekhlafi, M; Dippel, D; Campbell, B; Mitchell, P; Hill, M; Demchuk, A; Jovin, T; Davalos, A; Majoie, C; Saver, J; et al.
Abstract : Background: The Society of Neurointerventional Surgery (SNIS) revised its' operational definition of Emergent Large Vessel Occlusion (ELVO) recently to include proximal M2 segment MCA occlusions. The American Stroke Guidelines however, continue to assign this occlusion site a lesser degree of evidence of benefit with EVT than Internal Carotid Artery or M1-MCA segment occlusions. Methods: Patient-level data from HERMES Collaboration trials were included. HERMES core lab identified all M2 segment MCA occlusions patients. M2 occlusions were classified based on location (proximal vs distal), territory supplied (superior vs inferior) and size (dominant vs co-dominant vs non-dominant). To account for between-trial differences, mixed-effects modeling was used. The primary outcome was mRS 0–2 at 90 days. Secondary outcomes were ordinal mRS and mRS 0–1 at 90 days, symptomatic ICH (sICH), NIHSS 0–2 at 24 hours and final mTICI. Results: 130 patients with M2-MCA occlusions (proximal n=116 vs distal n=14, superior division n=72 vs inferior n=58, dominant n=73 vs co-dominant n=50 vs non-dominant n=7) were included. Successful reperfusion (mTICI 2b) was seen in 59.2%. Treatment effect favored EVT over control (adjusted OR 2.39, 95% CI: 1.08 to 5.28, p=0.03) for mRS 0–2 at 90 days (58.2% with EVT vs 39.7% control respectively). The direction of benefit favored EVT over control for all other outcomes, although results did not meet the threshold for statistical significance for some (see Table). Treatment effect favoring EVT was maximal in patients with proximal M2 segment occlusions (adjusted OR 2.68, 95% CI: 1.13 to 6.37, p=0.02 for mRS 0–2 at 90 days, 57.1% EVT vs 37.7% control, respectively) with direction of benefit favoring EVT across most secondary outcomes [(cOR for 90 day mRS shift 1.95, 95% CI: 0.98 to 3.87 p=0.058), (adjusted OR for NIHSS 0–2 at 24 hour 6.09, 95% CI: 1.55 to 23.99, p=0.01)]. Benefit with EVT was seen in patients with superior vs inferior division occlusions and in dominant M2 occlusions, although did not reach significance. No sICH (0%) was noted in EVT-treated patients. Conclusion: Patients with proximal M2 segment MCA occlusions show robust gains in functional ability at 90 days with EVT despite relatively lower rates of successful reperfusion. Unadjusted and adjusted analysis of outcomes in patients with M2 segment MCA occlusions. Disclosures: B. Menon: None. S. Brown: None. M. Almekhlafi: None. D. Dippel: None. B. Campbell: None. P. Mitchell: None. M. Hill: None. A. Demchuk: None. T. Jovin: None. A. Davalos: None. C. Majoie: None. J. Saver: None. F. Guillemin: None. S. Bracard: None. P. White: None. K. Muir: None. M. Goyal: None.